ANALYSIS OF THE EFFECT OF COMMITMENT AND PARTICIPATION ON COOPERATIVE PERFORMANCE WITH INNOVATION AS INTERVENING VARIABLES IN COOPERATIVES IN SERDANG BEDAGAI DISTRICT - Adinda Nadila Azhari; Endang Sulistya Rini; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the Effect Analysis of Commitment and Participation on Cooperative Performance with Innovation as an Intervening Variable in Cooperatives in Kab. Serdang Bedagai. This study used primary and secondary data obtained by distributing questionnaires to all actively assisted cooperatives in the Serdang Bedagai district government area, totaling 72 cooperative units. The questionnaire that was distributed online consisted of profiles of respondents and consisted of several statements that were in accordance with the variables contained in this study. The type of research used in this research is to use an associative method with a quantitative approach. Associative research was conducted to determine whether there is influence between exogenous variables and endogenous variables. The results of the study show that organizational commitment directly has a positive and significant effect on cooperative innovation in Serdang Bedagai District. Directly member participation has a positive and significant effect on cooperative innovation in Serdang Bedagai District. Directly organizational commitment has a positive and significant effect on the performance of cooperatives in Serdang Bedagai Regency. Directly member participation has a positive and significant effect on the performance of cooperatives in Serdang Bedagai Regency. Cooperative innovation directly has a positive and significant effect on the performance of cooperatives in Serdang Bedagai District. Indirectly, organizational commitment has a positive and significant effect on the performance of cooperatives in Serdang Bedagai Regency through cooperative innovation.